Enhancing Allocentric Spatial Recall in Pre-schoolers through Navigational Training Programme - Boccia, Maddalena; Rosella, Michela; Vecchione, Francesca; Tanzilli, Antonio; Palermo, Liana; D'Amico, Simonetta; Guariglia, Cecilia; Piccardi, Laura (Frontiers in Neuroscience, 2017)
Unlike for other abilities, children do not receive systematic spatial orientation training at school, even though navigational training during adulthood improves spatial skills. We investigated whether navigational training programme (NTP) improved spatial orientation skills in pre-schoolers. We administered 12-week NTP to seventeen 4- to 5-year-old children (training group, TG). The TG children and 17 age-matched children (control group, CG) who underwent standard didactics were tested twice before (T0) and after (T1) the NTP using tasks that tap into landmark, route and survey representations. We determined that the TG participants significantly improved their performances in the most demanding navigational task, which is the task that taps into survey representation. This improvement was significantly higher than that observed in the CG, suggesting that NTP fostered the acquisition of survey representation. Such representation is typically achieved by age seven. This finding suggests that NTP improves performance on higher-level navigational tasks in pre-schoolers.